Software development for emergency bed management - Izabella Soares de Oliveira; Eliane de Fátima Almeida Lima; Rita Inês Casagrande da Silva; Karla Crozeta Figueiredo; Isabel Cussi Brasileiro Dias; Candida Caniçali Primo (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to describe the process of developing a software for emergency bed management. Methods: a participatory research based on User-Centered Design in four stages: 1) definition of requirements and structure elaboration; 2) generation of alternatives and prototyping; 3) tests; 4) implementation. Seminars were held with health professionals between May 21, 2018 and May 31, 2019 for the preparation and assessment of software content. Results: the software CuidarTech KRONOS was developed for emergency bed management using the kanban methodology. Final considerations: this software will assist professionals' and managers' decision-making providing more reliable data to enable the improvement of work processes and the quality of patient care. Developing a bed management software is innovative in the health field, and no articles were found describing this methodology.